(C)Overt : A Series of Exhibitions at P.S. 1. - Decter, Joshua (Long Island : P.S.1 The Institute for Art and Urban Resources, 1988)
Baim, Richard ; Balch, Clif ; Balk, Dennis ; Baratloo, Moji ; Bastiaans, Christiaan ; Bishop, James ; Bloom, Barbara ; Boigon, Brian ; Doran, Anne ; Fischli & Weiss ; Formisano, Diana ; Haraguchi, Noriyuki ; Information Fiction Publicité ; Scher, Julia ; Schrager, Victor ; Vilmouth, Jean-Luc ; Wurtz, B.
Engels
(C)Overt : A Series of Exhibitions at P.S. 1, P.S.1 The Institute for Art and Urban Resources, Long Island, January 17 - March 6, 1988
boek